TIME-DEPENDENT SURFACE SPECIATION OF OXALATE AT THE WATER-BOEHMITE (γ-ALOOH) INTERFACE: IMPLICATIONS FOR DISSOLUTION - Axe K.; Persson P. (My University, 2001)
The surface speciation of oxalate at the water-boehmite (γ-AlOOH) interface during adsorption and dissolution reactions was studied by means of attenuated total reflectance infrared spectroscopy. The structural interpretations of infrared (IR) data were based on comparison with results from theoretical frequency calculations. Two different surface complexes were identified: an inner-sphere complex with a bidentate five-membered chelate structure involving both carboxylate groups; and a hydrogen-bonded surface complex with no direct bonding to Al atoms. A scheme was developed by which the surface concentrations of these complexes could be determined from IR spectroscopy data. The concentration of the hydrogen bonded complex was shown to be strongly dependent on the experimental conditions, and the concentration of the inner-sphere complex was comparatively insensitive to the conditions within the studied experimental range. The dissolution data indicated that an excess of oxalate with respect to a critical surface concentration of oxalate was necessary to induce significant boehmite dissolution. Under dissolving conditions, the concentration of the inner-sphere complex was shown to be almost identical to this critical concentration and thus a stable entity.